Epigenetic regulation of complement C1Q gene expression - Pegoraro, Silvia; Balduit, Andrea; Mangogna, Alessandro; Kishore, Uday; Ricci, Giuseppe; Agostinis, Chiara; Bulla, Roberta (Frontiers in Immunology, 2024)
Human C1q is a multifaceted complement protein whose functions range from activating the complement classical pathway to immunomodulation and promoting placental development and tumorigenesis. It is encoded by the C1QA, C1QB, and C1QC genes located on chromosome 1. C1q, unlike most complement components, has extrahepatic expression by a range of cells including macrophages, monocytes and immature dendritic cells. Its local synthesis under the conditions of inflammation and for the purpose of removal of altered self requires its strict transcriptional regulation. To delve into C1Q transcriptional regulation and unravel potential epigenetic influences, we conducted an in silico analysis utilizing a range of online tools and datasets. Co-expression analysis revealed tight coordination between C1QA, C1QB, and C1QC genes. Strikingly, distinct epigenetic patterns emerged across various cell types expressing or lacking these genes, with unique histone marks and DNA methylation status characterizing their regulatory landscape. Notably, the investigation extended to tumor contexts, unveiled potential epigenetic roles in malignancies. The cell type and tumor-specific histone modifications and chromatin accessibility patterns underscore the dynamic nature of epigenetic regulation of C1Q, providing crucial insights into the intricate mechanisms governing the expression of these immunologically significant genes. The findings provide a foundation for future investigations into targeted epigenetic modulation, offering insights into potential therapeutic avenues for immune-related disorders and cancer mediated via C1q.